2014
DOI: 10.1111/gfs.12120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of applications of organic solid cattle manure on Hungarian vetch and barley intercropping mixtures grown on soils of different depths

Abstract: Sloping fields on soils of shallow depth to tillage are commonly left uncultivated in many parts of the world. This study was conducted to compare the effects on morphological traits, dry‐matter (DM) yield, legume ratio (LR), crude protein content (CP), crude protein yield (CP yield) and mineral concentrations (N, P, K, S, Ca, Cu, Fe, Mg, Mn, Na, B and Zn) of Hungarian vetch (Vicia pannonica Crantz.) and barley (Hordeum vulgare L.) grown in intercropping mixtures in response to three rates of organic solid cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(25 reference statements)
2
5
0
Order By: Relevance
“…This concentration was similar to the levels described by Raij et al (1997) and Yolcu (2015) and higher than levels observed by Moreira et al (1997) who reported significant differences in S concentration in dry mass on the basis of gypsum rates. However, Lloveras et al (2004) found no significant difference in S absorption when applying different doses of pig manure.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…This concentration was similar to the levels described by Raij et al (1997) and Yolcu (2015) and higher than levels observed by Moreira et al (1997) who reported significant differences in S concentration in dry mass on the basis of gypsum rates. However, Lloveras et al (2004) found no significant difference in S absorption when applying different doses of pig manure.…”
Section: Resultssupporting
confidence: 91%
“…A similar increase in P concentration was observed by Lloveras et al (2004) with applications of 25 and 50 m 3 ha -1 per year of pig manure to alfalfa. However, Salmeron et al (2010) found no differences in P concentrations when they applied different doses of swine manure in the Ebro Valley, Spain; similar observations were made by Yolcu (2015) with an application of cattle manure. On the other hand, Araujo et al (2011) found small differences in P concentrations with the application of cattle manure (20 Mg ha -1 ), however, the accumulation of P in shoots was significant, indicating the potential P supply by cattle manure.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations